Pelvic Actinomycosis - Jabeen, Sadaqat (Journal of Postgraduate Medical Institute, 2011)
Pelvic actinomycosis was considered to be extremely rare in the early 19th century. Now a days and specially since the late 1970s, pelvic actinomycosis in association with intrauterine contraceptive devices has been regarded as a not infrequent disease in Europe and in the United States. One hundred ninety cases have been reported in the western literature and over 300 in the world literature.